Smoking increases risk of complication after musculoskeletal surgery - Leyla Tümen; Lena Pollmann-Schweckhorst; Regina Breinbauer; Mohammad M. Hammour; Romina H. Aspera-Werz; Gunnar Blumenstock; Tina Histing; Maximilian M. Menger; Sabrina Ehnert; Andreas Nüssler (EXCLI Journal : Experimental and Clinical Sciences)
Smoking is the most significant and modifiable risk factor for a range of conditions, including cancer, cardiovascular and respiratory diseases. Furthermore, it significantly reduces bone mass and increases the risk of fragility fractures due to its detrimental effects on bone metabolism and regeneration. Moreover, smoking is a known cause of chronic systemic inflammation, leading to an imbalance of cytokines. Comprehending the pathological mechanisms that underlie cytokine production and its impact on post-surgical healing is essential to prevent post-surgical complications. The present study recruited a total of 1144 patients, including 897 patients, among them non-smokers (N = 413), current smokers (N = 201) and ex-smokers (N = 283). Human proteome profiler arrays were used to screen for smoking-dependent differences in the serum cytokine and protein profiles, after matching samples for age, gender, body mass index (BMI), alcohol use, and diabetes risk. Cytokines and immune checkpoint proteins such as CD28, B7-1, MIG, TGFb2 and IL-1a/b were quantified by ELISA. Our study demonstrates a comprehensive understanding of the relationship between smoking, the development of complications, the systemic immune inflammation index (SII) and cytokine/protein levels. We found that a comparison of non-smokers, former smokers, and active smokers in our study cohort did not exhibit significantly altered cytokine and protein serum levels although other studies reported differences between smokers and non-smokers. We were unable to identify single blood circulating markers that could predict complications in smokers after trauma. However, we found the ratio of women to men to be inverted between non-smokers and active smokers resulting in a ratio of 0.62 in smokers. Furthermore, we demonstrate a higher complication rate, longer hospitalizations and elevated SII values among smokers, indicating an involvement of the immune system.